Improvements in musculoskeletal health and computing behaviors: Effects of a macroergonomics office workplace and training intervention. (July 2017) - Robertson, Michelle M.; Huang, Yueng Hsiang; Lee, Jin
Abstract: Computer use and its association with musculoskeletal and visual symptoms is an escalating concern. Organizations are shifting to a more proactive injury prevention perspective. Accordingly, a macroergonomics intervention consisting of flexible workplace design and office ergonomics training was designed to examine the effects on worker's computing behaviors, postures, and musculoskeletal discomfort, and their relationship to psychosocial factors. Participants were assigned to either group: 1) no-intervention control 2) flexible Workplace-only (WP-only), and 3) flexible Workplace + Training (WP+T). Observational findings indicate both intervention groups experienced positive, significant changes in improved workstation arrangements and computing postures, with the WP+T intervention group exhibiting a higher, significant change of behavioral translation. Also, significant, positive relationships between observed postures and musculoskeletal discomfort/pain were found. The intervention effect was stronger when management was responsive to workers' ergonomics needs. This study suggests that a macroergonomics intervention can produce beneficial effects for office and computer workers and organizations. Highlights: Intervention groups showed significant improvements of large effect size in workstation arrangements and postures. The workplace + training intervention group showed better behavioral translation. Observed postures and musculoskeletal discomfort/pain were significantly linked. Intervention effect was stronger when management was responsive to employee's ergonomics needs.